(untitled) (Journal of Research Updates in Polymer Science, 2018)
The article highlights some recent trends in the bleaching of textile materials. An attempt has been made to compare the effect of electrochemical bleaching with conventional bleaching of cotton. Electric current is used in the preparation of a bleaching agent to replace bleaching powder. The sodium hypochlorite generated from electrolyte cell is sufficient to produce powerful bleaching agent with available chlorine. Electrochemical bleaching with sodium hypochlorite offers numerous advantages like prevention of effluent problem, economy, reliability, cleanliness, and convenience in working. Attempts have been made to use sodium perborate as a bleaching agent with potassium persulphate as an activator at lower temperature in combined pre treatment of cotton fabric. Experimental trials have been designed by using taguchi technique. This bleaching technique promises to be eco-friendly process. In yet another interesting work, effort has been taken to bleach the scoured cotton fabric with sodium perborate as bleaching agent and tetreacetyl ethylenediamine as bleaching activator. The concentrations of these chemicals, temperature and time of the treatment have been varied. The utilization of hydrogen peroxide is much higher as compared with that of conventional bleaching process. Other advantages include less requirement of water and energy, thereby satisfying needs of eco-friendly process, lesser loss in weight, tearing strength, and tensile strength, in comparison with conventional bleaching process without compromising whiteness index.